2015
DOI: 10.1016/j.physio.2015.03.2125
|View full text |Cite
|
Sign up to set email alerts
|

Somali women's view of physical activity—a focus group study

Abstract: Background: Physical inactivity presents a major public health challenge and is estimated to cause six to ten percent of the major non-communicable diseases. Studies show that immigrants, especially women, have an increased risk of non-communicable diseases compared to ethnic Swedes. Somali immigrant women have increased rates of overweight and obesity, low fitness levels and low levels of cardiorespiratory fitness compared to non-immigrant women. These findings suggest that Somali women are at increased risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(11 reference statements)
1
4
0
Order By: Relevance
“…They did not give priority for physical activity as they were concerned about finding jobs to afford living expenses. Similar results were found in Mohamed, Hassan, Weis, Sia, and Wieland (2014) and Persson, Mahmud, Hansson, and Strandberg (2014). Practicing exercise is a social value that may not persist in some refugee's lives before moving to Jordan.…”
Section: Discussionsupporting
confidence: 87%
“…They did not give priority for physical activity as they were concerned about finding jobs to afford living expenses. Similar results were found in Mohamed, Hassan, Weis, Sia, and Wieland (2014) and Persson, Mahmud, Hansson, and Strandberg (2014). Practicing exercise is a social value that may not persist in some refugee's lives before moving to Jordan.…”
Section: Discussionsupporting
confidence: 87%
“…Over the past five years, research has been focusing more on exploring refugees/immigrants' perspectives of and barriers to physical activity [29][30][31][32][33][34]. Several studies conducted among Somali and other refugee and immigrant communities with either youth or adults living in the U.S. or overseas indicated that the barriers to their being physically active included lack of motivation to/interest in physical activity, financial constraint, lack of social support for physical activity, lack of culturally appropriate physical activity resources, less opportunities to walk in a western country, unsafe outdoor physical activity, unsupportive social norms for physical activity, unsupportive moral norms for physical activity for females, and poor weather among other reasons provided [29][30][31][32][33][34]. For instance, Wieland and his colleagues [34] conducted a qualitative study during July and December 2011.…”
Section: Discussionmentioning
confidence: 99%
“…They enjoy doing activities together, and they respect their community/religious leaders and role models. The effectiveness of social support and a role model on physical activity among refugee and immigrant populations have also been suggested by the most recent literature [29][30][31][32][33][34]. And (3) Using objective measures to identify the participants' behavioral patterns for physical activity in order to pinpoint and fill any potential gaps relevant to participants' behavioral consistency.…”
Section: Discussionmentioning
confidence: 99%
“…Stereotypes about obesity can perpetuate low NEAT, promote bullying in children, and permit discrimination [35-38]. Religion, too, can factor into promoting sedentariness [39]. …”
Section: Cityscapes and Sittingmentioning
confidence: 99%